Pelanggaran Hak Cipta di Era Digital: Praktik Mod dalam Gim Interaktif Naratif - Raphael Bertrand Mayaka; Desty Puspita Maharani (Universitas Wahid Hasyim, 2024)
This article intents to explores the issue of copyright infringement in the digital age, with a specific focus on the practice of modding within interactive narrative games. As the gaming industry continues to evolve, the boundary between user-generated content and intellectual property rights becomes increasingly blurred, raising significant legal and ethical concerns. Through a normative approach, this research employs three methodologies: the conceptual approach to define the nature of modding and copyright, the statutory approach to analyze existing laws and regulations governing intellectual property in digital contexts, and the case approach to examine real-world instances of copyright violations in the realm of narrative games. The findings highlight the challenges in balancing creativity and legal protection in an era where users are both creators and consumers. This study provides recommendations for enhancing legal frameworks to better address the complexities of digital content creation, ensuring both the protection of copyright holders and the continued innovation within the gaming community.